Mob control : models of threshold collective behavior /: models of threshold collective behavior. (2017) - Breer, Vladimir V; Novikov, D. A (Dmitriĭ Aleksandrovich), 1970-; Rogatkin, A. D (Andreĭ Dmitrievich)
No abstract available